INTERRUPTIONS PRODUCED BY THE MOLLUCAN STUDENTS IN THE FELLOWSHIP MEETING - Marcelin A. Silalebit; Henny P.S. Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This thesis is about a study of the interruptions produced by the Moluccan students in a fellowship meeting, consisting of fifteen students as the respondents, who are divided into two: the chairperson and the members. The purposes of the study are to know the tokens and the functions of interruptions used by the chairperson and the members of the meeting by considering social role as the social factor. The writer applies the theory of interruptions by Tannen (1990) and Wardhaugh (1985) as the main theories. Besides, the writer also uses the theory of social role by Johnstone (2008) and the theory of discourse markers by Schiffrin (2003) as the supporting theories. The writer used qualitative approach to conduct this research. The writer discovered that the chairperson produced more tokens (19) than the members (13). Moreover, the writer found that the respondents produced Ambonese tokens, such as “Hiii”, “Weee”, “Seng”, “Eee”, and Suroboyoan tokens, such as “Lho” and “Itulho”. Both the chairperson and the members produced “other” functions the most with 58.75% and 63.81%. In conclusion, social role influenced the interruptions and their functions, and the number of tokens produced by the participants.